ANÁLISES DA ADOÇÃO DO PREÇO HORÁRIO NO BRASIL - Oliveira, Helena (2020)
This assignment will assist in understanding the benefits that the hourly pricing endorsement in the electric energy pricing, under DESSEM’s mathematical model’s technical support, will bring upon the energy’s acquisition and consumption management. Analisys will seek to expain and report topics or events, either precedent or related, in order to more easily comprehend these subjects. A reading of the hourly pricing’s shadow accounting will be had, where the Settlement Price Differences (PLD) accrual will be marked out, according to the highest granularity. Following that, DESSEM’s shadow operation will be evaluated, in order to find out whether or not it registers clues that the model is ready and working consistently and stably. Finally, a contemplation of the aspects of energy commercialization, looming the general dificulties and it’s segment challenges, will function in the deliberation about the powerful structural decisions for the energy market to integrally absorb the hourly pricing proposal.